Pain Threshold, Pain Severity and Sensory Effects of Pain in Fibromyalgia Syndrome Patients: A new scale study - Ankarali, Handan; Ataoglu, Safinaz; Ankarali, Seyit; Guclu, Hasan (Bangladesh Journal of Medical Science, 2018)
Objectives: The aim of this study to develop a new scale to evaluate pain threshold, sensory effects of pain and pain severity in patients with Fibromyalgia Syndrome (FMS). Material and Methods: This is a cross-sectional survey study and a questionnaire was administered to 52 voluntary patients diagnosed with FMS. In the proposed scale, thereare six questions about severe and less severe pain experience,two questions about the pain severity and sensory effect of FMS. In statistical analysis we used reliability analysis, factor analysis for construct validity, and other statistical tests to compare differences. Results: Exploratory factor analysis showed construct validity of the scale, and detected three factors. The internal consistency of the items of the scale was statistically significant. The agreement between the scores was good. Based on the answers, the patients were divided into two groups as low and high pain thresholds. There was no significant difference between these two groups in terms of severity of pain and sensory change due to fibromyalgia. In addition, the severity of pain in patients is lower than headache and at the level of stomachache and toothache. Discussion and Conclusion: The proposed scale allows the assessment of pain severity to be more detailed and paying attention to visually, it allows determining the pain threshold. It is suggested to compare the pain threshold determined by this scale with the pain threshold determined by different methods. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.342-350